Anti-cancer effect of the polysaccharide extract from the Ganoderma lucidum against HeLa cell lines - K. Mohan; A. M. Padmanaban; V. Uthayakumar; R. Chandrasekhar; T. Muralisankar; E. Chithra (Bangladesh Pharmacological Society, 2017)
No abstract is available